Penerapan teknologi blockchain berbasis smart contract untuk meningkatkan keamanan transaksi finansial online - Wirayuda, Steven Aprianto; Lailiyah, Siti; Fajri, Ahmad (Universitas Trunojoyo Madura, 2025)
The digital transformation in the financial sector demands a transaction system that is not only fast and efficient but also secure and transparent. This study explores the application of blockchain technology as a solution to the problems found in centralized online financial transaction systems that are vulnerable to manipulation. The objective of this research is to design a blockchain-based financial transaction security system architecture that can be evaluated through a conceptual simulation approach. This study uses a descriptive qualitative method with tools such as Ganache, MetaMask, and Remix IDE to simulate smart contract-based transactions within a local blockchain environment. The novelty of this research lies in the integration of a security system modeling approach with realistic scenario-based simulations, which is rarely discussed in previous studies. The research contributes by producing a modular system architecture that integrates key components—users, smart contracts, validators, and regulators—into a cohesive workflow applicable to various digital financial platforms. Simulation results show that the proposed system enhances security, accelerates transaction validation, strengthens auditability, and reduces operational costs compared to conventional transaction systems. This study provides a strong foundation for the broader development of blockchain-based financial systems that are more resistant to external attacks.Keywords: System Architecture, Blockchain, Transaction Security, Smart Contract, Simulation